Effect of molding processes on multiaxial fatigue strength in short fibre reinforced polymer - Takahiko Sawada; Hiroshi Aoyama (Fracture and Structural Integrity, 2016)
This study concerns the multiaxial static and fatigue strength properties. Short-glass-fibre-reinforced phenolic-resin composites (SGP) molded by injection and compression processes were subjected to tensiontorsion combined static and fatigue tests at room temperature under various test conditions. Tension – torsion combined static strength well agreed with Tsai-Hill failure criteria without depending on processes. Relationships between the maximum principal stress, σp1, max, and the number of fracture cycles, Nf, were approximately linear in the whole range of up to 106 cycles. For a unified evaluation of multiaxial fatigue life for SGP, non-dimensional effective stress, σ*, defined by modifying Tsai-Hill failure criteria was applied. The slopes of σ*- Nf curves according to Baskin’s law were almost identical to the injection (n = 26.3) and compression (n = 26.2). We finally confirmed that the multiaxial fatigue life of SFRP could be predicted by using σ* with a unique Wöhler curve without relying on molding processes